A spatial distribution effect of almond shell bio filler on physical, mechanical, thermal deflection and water absorption properties of vinyl ester polymer composite. Issue 5 (26th March 2022) - Palaniyappan, Sabarinathan; Veiravan, Annamalai; Kaliyamoorthy, Rajkumar; Kumar, Vishal; Veeman, Dhinakaran
Abstract: The present work deals with the effective utilization of almond shell bio‐waste fillers in the production of vinyl ester polymer composites. The almond shell particle surface was chemically modified by alkaline treatment. The almond shell particles with varying weight percentages of 5%–30% were used to prepare the vinyl ester polymer composite. The experimental results show that a 25% addition of alkaline‐treated almond shell particles significantly improved the mechanical properties of the composite when compared to pure vinyl ester and untreated almond‐filled composite samples. The highest tensile, flexural, impact strength, and Shore D hardness of the 25% alkaline‐treated almond shell composite were 54, 142 MPa, 31, and 79 kJ/m 2, respectively. This was due to the alkaline treatment of almond shell particles, which improved the interfacial adhesion between the vinyl ester matrix and almond particles. The heat deflection temperature of the 25% alkaline treated almond shell particle‐filled vinyl ester matrix composite was 72°C. The thermal insulating characteristics of alkali‐treated almond shells were improved due to the reduction of quickly thermal degradable materials such as hemicelluloses and lignin, as indicated by Fourier transform infrared spectroscopic data, and more exposure of minerals to the surface, as confirmed by energy dispersive X‐ray analysis. The addition of alkaline‐treated almond shell particles improves the characteristics of the vinyl ester matrix and allows the development of biocomposites. Abstract :